Pemanfaatan Limbah Industri Pengolahan Kayu Sebagai Sumber Energi Arang Alternatif di Kota Jayapura - Jefri F.N. Maurits; Audry F. Walukow; Johnson Siallagan (Jurnal Biologi Papua, 2023)
The waste of sawdust and wood chips in the wood processing industry in Jayapura City has not been utilized properly and maximally, but only as firewood. In fact, this waste has a large enough potential to be developed as a raw material for making charcoal briquettes. This research method analyzed the calorific value of 5 (five) treatments using Completely Randomized Design, using 5 (five) repetitions so that the total treatment was 25 (twenty five). The treatment in this study was T0: 100% sowang wood charcoal, T1: sawdust/merbau wood chips (90%) + 10% tapioca flour, T2 : sawdust/merbau wood chips 70% + sawdust/mixed jungle wood chips 20% + 10% tapioca flour, T3: 45% merbau sawdust/wood chips + 45% mixed jungle sawdust/wood chips + 10% tapioca flour, T4: 20% merbau sawdust/wood chips + sawdust/wood chips mixed jungle 70% + 10% tapioca flour. The results showed that T0: 100% sowang wood charcoal produced the highest calorific value, namely 7,619 cal/gram compared to other treatments. The highest calorific value of charcoal briquettes is the T2 calorific value treatment: 70% merbau sawdust/chip + 20% mixed sawdust/jungle wood chips + 10% tapioca flour, with a calorific value of 6,230 cal/gram and charcoal briquettes when it has been produced regularly commercially, grilled fish traders and satay traders are willing to use charcoal briquettes from wood processing industry waste. Key words: wood waste; alternative fuel; charcoal briquettes.